Divergent LysM effectors contribute to the virulence of Beauveria bassiana by evasion of insect immune defenses. - Kai Cen; Bing Li; Yuzhen Lu; Siwei Zhang; Chengshu Wang (PLoS Pathogens)
The lysin motif (LysM) containing proteins can bind chitin and are ubiquitous in various organisms including fungi. In plant pathogenic fungi, a few LysM proteins have been characterized as effectors to suppress chitin-induced immunity in plant hosts and therefore contribute to fungal virulence. The effector mechanism is still questioned in fungus-animal interactions. In this study, we found that LysM proteins are also present in animal pathogenic fungi and have evolved divergently. The genome of the insect pathogen Beauveria bassiana encodes 12 LysM proteins, and the genes were differentially transcribed by the fungus when grown in different conditions. Deletion of six genes that were expressed by the fungus growing in insects revealed that two, Blys2 and Blys5, were required for full fungal virulence. Both proteins could bind chitin and Blys5 (containing two LysM domains) could additionally bind chitosan and cellulose. Truncation analysis of Blys2 (containing five LysM domains) indicated that the combination of LysM domains could determine protein-binding affinity and specificity for different carbohydrates. Relative to the wild-type strain, loss of Blys2 or Blys5 could impair fungal propagation in insect hemocoels and lead to the upregulation of antifungal gene in insects. Interestingly, the virulence defects of ΔBlys2 and ΔBlys5 could be fully restored by complementation with the Slp1 effector from the rice blast fungus Magnaporthe oryzae. In contrast to Slp1 and Blys2, Blys5 could potentially protect fungal hyphae against chitinase hydrolysis. The results of this study not only advance the understanding of LysM protein evolution but also establish the effector mechanism of fungus-animal interactions.